Research status of gas sensing performance of Ti3C2Tx-based gas sensors: A mini review - Peng, Bo; Huang, Xinlu (Frontiers in Chemistry, 2022)
Developing efficient gas sensing materials capable of sensitive, fast, stable, and selective detection is a requisite in the field of indoor gas environment monitoring. In recent years, metal carbides/nitrides (MXenes) have attracted attention in the field of gas sensing because of their high specific surface area, good electrical conductivity, and high hydrophilicity. Ti3C2Tx, the first synthesised MXene material, has also become the most popular MXene material owing to its low formation energy. In this paper, the latest progress in the application of Ti3C2Tx-based nanomaterials in the field of gas sensors is reviewed. Some challenges currently faced by Ti3C2Tx gas sensors are discussed, and possible solutions are proposed, focusing on the use of composite materials and surface functionalization methods to modify Ti3C2Tx nanomaterials to improve their sensing performance for the detection of gaseous volatile organic compounds. This study highlights the application prospects of Ti3C2Tx nanomaterials in gas sensors.